2019
DOI: 10.1177/1071181319631168
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Visual Attention of Pairs of Operators during a Low to High Workload Change

Abstract: Dynamic and data-rich domains, like those found in the military, primarily rely on multiple operators’ visual attention. Of interest is to understand how shared visual attention impacts performance when workload changes and whether this informs the adaptation process between collaborators. Ten pairs of participants completed a simulated Unmanned Aerial Vehicle control task under two different workload conditions - first under low workload and then under high workload. The best and worst performing pairs were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Following this guideline, no participants were excluded from the study and the mean data loss was 9.23%. Given, previous work showed that the best performing pairs had higher percent gaze overlap on the target AOI (Devlin et al, 2019), percent gaze overlap was then calculated for each minute of the scenario for the target AOI only. The best performing pairs' percent gaze overlap ranged for each scenario (low workload range: 17.4-33.0%; high workload range: 40.0-63.7%) and were consistently higher than worst performing pairs, (low workload range: 1.0-7.3%; high workload range: 9.9-22.2%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following this guideline, no participants were excluded from the study and the mean data loss was 9.23%. Given, previous work showed that the best performing pairs had higher percent gaze overlap on the target AOI (Devlin et al, 2019), percent gaze overlap was then calculated for each minute of the scenario for the target AOI only. The best performing pairs' percent gaze overlap ranged for each scenario (low workload range: 17.4-33.0%; high workload range: 40.0-63.7%) and were consistently higher than worst performing pairs, (low workload range: 1.0-7.3%; high workload range: 9.9-22.2%).…”
Section: Resultsmentioning
confidence: 99%
“…This research builds on previous work that examined whether shared visual attention affected the collaboration strategies of successful and unsuccessful pairs managing a workload change (Devlin, Flynn, & Riggs, 2019). Our previous work found the most successful pairs of participants adapted both their task completion and shared visual attention strategies more readily upon experiencing a change in workload.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Table 2 shows the point value associated with each task (Devlin et al, 2019). Points were assigned to emphasize the priority of the primary task (i.e., target detection) as well as to convey the severity of incorrectly or not attending to a task (e.g., UAV flies through no-fly-zone ).…”
Section: Methodsmentioning
confidence: 99%